2007
DOI: 10.1038/ismej.2007.45
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of chaotic instability in biological nitrification

Abstract: Biological nitrification (that is, NH 3 -NO 2 À -NO 3 À ) is a key reaction in the global nitrogen cycle (Ncycle); however, it is also known anecdotally to be unpredictable and sometimes fails inexplicably. Understanding the basis of unpredictability in nitrification is critical because the loss or impairment of this function might influence the balance of nitrogen in the environment and also has biotechnological implications. One explanation for unpredictability is the presence of chaotic behavior; however, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(201 citation statements)
references
References 40 publications
8
192
1
Order By: Relevance
“…This suggests that there is no unifying environmental selection across the group of microcosms; rather, the complex dynamics caused by community-environment feedbacks and interspecies interactions, and/or stochastic effects, create different selective environments in replicate microcosms. In our microcosms, metabolic feedbacks may lead to non-linear ecosystem dynamics, potentially producing chaotic or initial condition-dependent trajectories as observed in other studies (Becks et al, 2005;Graham et al, 2007;Benincà et al, 2008). Indirect interspecies interactions mediated by the physical environment are also likely to have a key role in our microcosms: for example, the generation of an anaerobic state as a result of cellulose degradation and sulphate reduction, which will strengthen selection for anaerobes in the developing community.…”
Section: Predictability Of Microbial Ecosystem Developmentmentioning
confidence: 93%
“…This suggests that there is no unifying environmental selection across the group of microcosms; rather, the complex dynamics caused by community-environment feedbacks and interspecies interactions, and/or stochastic effects, create different selective environments in replicate microcosms. In our microcosms, metabolic feedbacks may lead to non-linear ecosystem dynamics, potentially producing chaotic or initial condition-dependent trajectories as observed in other studies (Becks et al, 2005;Graham et al, 2007;Benincà et al, 2008). Indirect interspecies interactions mediated by the physical environment are also likely to have a key role in our microcosms: for example, the generation of an anaerobic state as a result of cellulose degradation and sulphate reduction, which will strengthen selection for anaerobes in the developing community.…”
Section: Predictability Of Microbial Ecosystem Developmentmentioning
confidence: 93%
“…Nitrification and denitrification are closely associated in soils, especially at aerobicanaerobic interfaces where the nitrification product, nitrate (NO 3 À ), is readily available for reduction (Nicolaisen et al, 2004;Seitzinger et al, 2006), although recent evidence indicates that this relationship may exhibit chaotic behavior due to the dynamics of the mutualistic relationship between ammonia-oxidizing and nitrite-oxidizing bacteria (Graham et al, 2007). If mineralization promotes nitrification, this may in turn stimulate denitrification and the interaction between these processes could increase nitrous oxide (N 2 O) production at many stages in this complex cycle (Paul and Clark, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al (2006) argue that this reflects optimization of pathway length to maximize energy production, and that because NO 2 À oxidation is energetically less favorable, it must occur more rapidly than NH 3 oxidation and consume NO 2 À nearly instantaneously. However the coupling between these groups is fundamentally unstable: Graham et al (2007) demonstrated that perturbation of NH 3 oxidation in bioreactors lead to chaotic behavior among NOB, and evidence for such temporal decoupling in the ocean was observed off southern California (Beman et al, 2010). NH 3 and NO 2 À oxidation can also be decoupled spatially; light is thought to directly or indirectly inhibit NH 3 -oxidizing Archaea, NH 3 -oxidizing bacteria and NOB to varying degrees, with NOB being more sensitive (reviewed by Lomas and Lipschultz (2006).…”
Section: Introductionmentioning
confidence: 99%